2009
DOI: 10.1177/147323000903700127
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Coeliac Disease Antibodies in Patients with Ankylosing Spondylitis: A Case-Controlled Study

Abstract: The presence of anti-gliadin antibodies (AGA) and their relationship with intestinal permeability and prevalence of undiagnosed coeliac disease (CD) in ankylosing spondylitis (AS) were investigated. Blood samples from 30 AS patients and 19 age- and sex-matched controls were analysed for human leucocyte antigen (HLA)-B27, AGA and endomysial antibodies (EMA). Immunoglobulin (Ig) A-type AGA and IgG-type EMA were determined by enzyme-linked immunosorbent assay. AGA-positive patients were examined by gastroduodenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
1
15
1
1
Order By: Relevance
“…Our study confirms prior findings of elevated CD-associated antibodies in patients with SpA [47], extending these observations for the first time to pediatric SpA. We also confirm prior observations of elevated total serum IgA levels in SpA patients [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirms prior findings of elevated CD-associated antibodies in patients with SpA [47], extending these observations for the first time to pediatric SpA. We also confirm prior observations of elevated total serum IgA levels in SpA patients [15].…”
Section: Discussionsupporting
confidence: 92%
“…However, there is contradictory data with respect to the presence of antibodies associated with CD in patients with pediatric or adult arthritis. Several studies have identified increased anti-gliadin IgA or anti-tissue transglutaminase (TTG) IgA antibodies in adults with psoriatic arthritis (PsA) or ankylosing spondylitis (AS) [47], while others found no differences in antibody titers [8, 9]. Similar data exist in children, and several studies have shown increased frequency of CD-associated antibodies in patients with JIA [10–13], although none of the studies evaluated children with SpA.…”
Section: Introductionmentioning
confidence: 99%
“…Also, no association could be demonstrated with the occurrence of peripheral arthritis or uveitis. Also, no relationship of CeD and the presence of EmAIgA could be found agreeing with the findings of Riente et al [6] but contrary to Togrol et al [7]. Such discrepancy could be explained by the fact that CeD is a very common disease (affecting 1:300 to 1:500 of the general population) [14] and a coincidence of these two diseases can be due to a false positive caused by the small sample number studied rather than to a true association.…”
Section: Discussioncontrasting
confidence: 66%
“…Riente et al [6] found no increased prevalence of anti-tissue transglutaminase (tTG) in ankylosing spondylitis and psoriatic arthritis patients, but Togrol et al [7] found a prevalence of 10% of anti-endomysial (EmA) positivity. EmA-IgA as well as anti-tTG has allowed evaluating the potential risk for CeD in individuals with suggestive symptoms and in high-risk populations.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of anti-gliadin antibodies (AGA) has been abandoned as a test for CD diagnosis due to their poor specificity for the disease. However, AGA of the class IgG has been previously reported as a possible biomarker of increased intestinal permeability [10], [11].…”
Section: Introductionmentioning
confidence: 99%